Epidemiology of infection with lung worms in sheep in Tikrit city, Salah Al Deen province - Abed Fayadh Ali Alageely; Tawfiq Ibrahim Al-Alusi (Tikrit Journal of Pure Science, 2023)
1.The study area spend Tikrit in Salah Aden province, and followed him from the aspects and villages and tubing such as Al-Alam district , Hawi Albu-Ajeel, Al-Naama areas, a series Hamrin mountains east of the Tigris River, stretching from north to south and Al Awja district, Aouinat,  Mahzm, Al-Hamra and al-Jazeera to Lake Tharthar west of the Tigris River.